2013
DOI: 10.1371/journal.pone.0059838
|View full text |Cite
|
Sign up to set email alerts
|

Early Weaning Stress in Pigs Impairs Innate Mucosal Immune Responses to Enterotoxigenic E. coli Challenge and Exacerbates Intestinal Injury and Clinical Disease

Abstract: Background and AimsThe clinical onset and severity of intestinal disorders in humans and animals can be profoundly impacted by early life stress. Here we investigated the impact of early weaning stress in pigs on intestinal physiology, clinical disease, and immune response to subsequent challenge with enterotoxigenic F18 E. coli (ETEC).MethodologyPigs weaned from their dam at 16 d, 18 d, and 20 d of age were given a direct oral challenge of F18 ETEC at 26 d of age. Pigs were monitored from days 0 to 4 post-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
177
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(195 citation statements)
references
References 46 publications
5
177
0
1
Order By: Relevance
“…However, physiological and/or psychological stresses such as weaning lead to dysfunctional of gut microbial composition (McLamb et al, 2013). By supplementing probiotics to the piglets feeding during post weaning, there is a potential to modulate intestinal microbial diversity by improving the establishment of beneficial bacterial populations for health and reducing pathogenic bacteria such as enterotoxigenic E. coli (Brousseau, et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, physiological and/or psychological stresses such as weaning lead to dysfunctional of gut microbial composition (McLamb et al, 2013). By supplementing probiotics to the piglets feeding during post weaning, there is a potential to modulate intestinal microbial diversity by improving the establishment of beneficial bacterial populations for health and reducing pathogenic bacteria such as enterotoxigenic E. coli (Brousseau, et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…coli LPS induces morphological and histological changes in the intestine of weaned piglets, such as: atrophy of villi, increase in crypt depth, and injury to the epithelial barrier (Ospina et al ., 2011;Parra et al ., 2011;Montoya et al ., 2012;McLamb et al ., 2013). LPS also induces morphological changes in goblet cells, which cause variations in their proliferative activity in different organs (Shimizu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although current vaccine developments against ED have concentrated on antitoxin and anticolonization immunity, CMI still plays a pivotal role in providing protection against ED during post-weaning (Haesebrouck et al 2004;McLamb et al 2013). In this study, we observed an increased SI (Figure 4(IV)) and a significant elevation of INF-g ( Figure 5), which is a marker of CMI in the splenic T cell, of primed mice that were individually pulsed with Stx2eB, FedF, and FedA.…”
Section: Discussionmentioning
confidence: 56%